2004
DOI: 10.1677/joe.1.05703
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of nestin and insulin and expression of islet cell markers in long-term human pancreatic nestin-positive cell cultures

Abstract: Strategies to differentiate progenitor cells into cells in vitro have been considered as an alternative to increase cell availability prior to transplantation. It has recently been suggested that nestin-positive cells could be multipotential stem cells capable of expressing endocrine markers upon specific stimulation; however, this issue still remains controversial. Here, we characterized short-and longterm islet cell cultures derived from three different human islet preparations, with respect to expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
1
20
0
4
Order By: Relevance
“…30 To characterize the phenotype of proliferating-islet-derived cells in the initial days of culture, we analyzed the expression of nestin, an intermediate filament present in several undifferentiated precursor cells that has been found to be expressed in cultured islet cells under different conditions. [10][11][12] Nestin expression has been reported to precede the appearance of b-cells during embryogenesis 13 and to represent a possible marker of adult b-cell precursors. 11,36 In our study, we observed that hPIDM cells appear to emerge from a mixed cell population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 To characterize the phenotype of proliferating-islet-derived cells in the initial days of culture, we analyzed the expression of nestin, an intermediate filament present in several undifferentiated precursor cells that has been found to be expressed in cultured islet cells under different conditions. [10][11][12] Nestin expression has been reported to precede the appearance of b-cells during embryogenesis 13 and to represent a possible marker of adult b-cell precursors. 11,36 In our study, we observed that hPIDM cells appear to emerge from a mixed cell population.…”
Section: Resultsmentioning
confidence: 99%
“…6 Additional studies suggested that progenitor cells may reside within the pancreatic ductal epithelium 2-7 or in the acinar tissue. 8,9 Nevertheless, the exact nature and localization of adult pancreatic stem/ progenitor cells remains controversial [9][10][11][12][13][14][15][16] and their existence in vivo, at least in mice, has recently been questioned. 6 Recent evidence has shown that human embryonic stem cells are able to differentiate into insulin-producing cells in vitro, thus potentially leading to an unlimited source of cells for transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The change mechanism of the intracellular organisations is still not fully understood in various situations such as mitosis, differentiation and different pathological conditions of dynamic structure of intermediate fi lament proteins (26,27). The word nestin is an acronym of neuroepithelial stem cell protein (28) and it is a type VI intermediate fi lament protein forming bundles in neuroepithelial stem/progenitor cells in the growing central nervous system of rat embryos and in humans (20,30). Nestin was expressed mostly in the progenitor cells of developing and innovating tissues in early periods of neural development and in CNS stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin was fi rst identifi ed in mitotically active central and peripheral nervous system stem/progenitor cells that give rise to both neurons and glia during early neurogenesis (13,14). It is also detected in some adult stem/progenitor cells; such as newborn vascular endothelial cells (15)(16)(17), striated muscle precursor cell (18), hair follicle precursor cell (19), islet precursor cell (20) and liver oval cell (21). Nestin may represent the proliferation, migration and multi-differentiated characteristics of multi-lineage progenitor cells (11).…”
mentioning
confidence: 99%